Leveraging human-robot interaction in hospitality services: Incorporating the role of perceived value, empathy, and information sharing into visitors' intentions to use social robots. (June 2020) - de Kervenoael, Ronan; Hasan, Rajibul; Schwob, Alexandre; Goh, Edwin
Abstract: Social robots have become pervasive in the tourism and hospitality service environments. The empirical understanding of the drivers of visitors' intentions to use robots in such services has become an urgent necessity for their sustainable deployment. Certainly, using social androids within hospitality services requires organisations' attentive commitment to value creation and fulfilling service quality expectations. In this paper, via structural equation modelling (SEM) and semi-structured interviews with managers, we conceptualise and empirically test visitors' intentions to use social robots in hospitality services. With data collected in Singapore's hospitality settings, we found visitors' intentions to use social robots stem from the effects of technology acceptance variables, service quality dimensions leading to perceived value, and two further dimensions from human robot interaction (HRI): empathy and information sharing. Analysis of these dimensions' importance provides a deeper understanding of novel opportunities managers may take advantage of to position social robot-delivered services in tourism and hospitality strategies. Graphical abstract: Image 1 Highlights: Social robots have now become pervasive in hospitality service environment. Understanding the drivers of visitors' intention to use social robots is central to assist sustainable deployment. Results show that visitors' intentions to use social robots stem from perceived value, empathy and information sharing. Results provide a deeper understanding of opportunities for service strategy managers need to take advantage of. Novel roles for human employees are being drawn.